Teaching tourism in the Anthropocene: New technologies, fieldwork, and student involvement - Sandra Ricart; Bas Amelung (Investigaciones Geográficas)
Humanity has affected almost every ecosystem on Earth; it has even changed how the Earth works, ushering in a new geological epoch: the Anthropocene. Climate change, biodiversity loss and the growing plastic soup in the oceans are all facets of this new epoch. Tourism is a main force behind the emergence of the Anthropocene and is also greatly impacted by it. To learn to live within the Earth’s bounds requires a paradigm change that transcends the ‘old ways of doing things’. Education offers our best chance of endowing new generations of professionals with the knowledge and skills to bring this paradigm change about, also in tourism. This Special Issue provides examples of methods, tools, and approaches to address environmental challenges and sustainable gaps in tourism education. The collection of articles emphasises the relevance of new technologies, fieldwork, and student involvement as building blocks for new teaching paradigms in response to the environmental challenges and tourism dynamics occurring in the Anthropocene.